Ten Things Every Geriatrician Should Know About House Calls. Issue 1 (28th November 2018) - Yang, Mia; Thomas, Jantira; Zimmer, Rachel; Cleveland, Maryjo; Hayashi, Jennifer L.; Colburn, Jessica L.
Abstract : Home‐based primary care (HBPC) is experiencing a reemergence to meet the needs of homebound older adults. This brief review based on existing literature and expert opinion discusses 10 key facts about HBPC that every geriatrician should know: (1) the team‐based nature of HBPC is key to its success; (2) preparations and after‐hour access for house calls are required; (3) home safety for the clinician and patient must be considered; (4) being homebound is an independent mortality risk factor with a high symptom burden; (5) home care medicine presents unique benefits and challenges; (6) a systems‐based approach to care is essential; (7) HBPC is a sustainable model within value‐based care proven by the Department of Veterans Affairs and the Independence at Home Medicare Demonstration Project; (8) HBPC has an educational mission; (9) national organizations for HBPC include American Academy of Home Care Medicine and Home Centered Care Institute; and (10) practicing HBPC is a privilege. HBPC is a dynamic and unique practice model that will continue to grow in the future.J Am Geriatr Soc 67:139–144, 2019.